2018
DOI: 10.1590/1982-0224-20170094
|View full text |Cite
|
Sign up to set email alerts
|

Peixes da planície de inundação do alto rio Paraná e áreas adjacentes: revised, annotated and updated

Abstract: The book “Peixes da planície de inundação do alto rio Paraná e áreas adjacentes” represents the most cohesive data compilation for the rio Paraná floodplain. However, considering the dynamicity of the taxonomy of freshwater fishes, several new records and taxonomic changes occurred along the past years. Therefore, the results of that publication were revisited, providing an update of the species list, their taxonomic status, records and geographic distribution, and also new keys for genera and species. The spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
159
1
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(200 citation statements)
references
References 106 publications
(133 reference statements)
6
159
1
14
Order By: Relevance
“…The third species of the genus, P. mesopotamicus , is restricted to Paraná‐Paraguay River basin (Fricke et al, ; Jégu, ; Ota et al ., ). Piaractus mesopotamicus possesses morphological differences that distinguish it from its two congeners, such as tiny scales on the body, reflected in more lateral line scales (107–128 vs .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The third species of the genus, P. mesopotamicus , is restricted to Paraná‐Paraguay River basin (Fricke et al, ; Jégu, ; Ota et al ., ). Piaractus mesopotamicus possesses morphological differences that distinguish it from its two congeners, such as tiny scales on the body, reflected in more lateral line scales (107–128 vs .…”
Section: Discussionmentioning
confidence: 97%
“…The third species of the genus, P. mesopotamicus, is restricted to Paraná-Paraguay River basin (Fricke et al, 2018;Jégu, 2003;Ota et al, 2018). Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding of Geophagus sveni in the Paraná River in Argentina constitutes the first report of the genus Geophagus sensu stricto from the country; although the presence of the genus in the Paraná river basin has been suggested since 2007, with reports of G. proximus (Graça and Pavanelli 2007, Moretto et al 2008, Gois et al 2015. The first report of G. sveni in the Upper Paraná river basin is an updated checklist of fishes from the Upper Paraná floodplain by Ota et al (2018). These authors reassigned specimens previously reported as Geophagus cf.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Amazon native Geophagus proximus (Castelnau, 1855) has been recorded from reservoirs of the Upper Paraná river basin in Brazil since the early 2000s (Graça and Pavanelli 2007, Moretto et al 2008, Gois et al 2015, there were no records of the genus from the Argentine stretch until now (Mirande and Koerber 2015). In a recently published update to Graça and Pavanelli (2007), Ota et al (2018) determined as Geophagus sveni Lucinda, Lucena & Assis, 2010 specimens previously assigned to Geophagus cf. proximus.…”
Section: Introductionmentioning
confidence: 99%